The Novel Avian Leukosis Virus Subgroup K Shares Its Cellular Receptor with Subgroup A - Přikryl, David; Plachý, Jiří; Kučerová, Dana; Koslová, Anna; Reinišová, Markéta; Šenigl, Filip; Hejnar, Jiří (Journal of virology, 2019)
Avian leukosis virus subgroup K (ALV-K) is composed of newly emerging isolates, which, in sequence analyses, cluster separately from the well-characterized subgroups A, B, C, D, E, and J. However, it remains unclear whether ALV-K represents an independent ALV subgroup with regard to receptor usage, host range, and superinfection interference. In the present study, we examined the host range of the Chinese infectious isolate JS11C1, an ALV-K prototype, and we found substantial overlap of species that were either resistant or susceptible to ALV-A and JS11C1. Ectopic expression of the chicken tva gene in mammalian cells conferred susceptibility to JS11C1, while genetic ablation of the tva gene rendered chicken DF-1 cells resistant to infection by JS11C1. Thus, tva expression is both sufficient and necessary for JS11C1 entry. Receptor sharing was also manifested in superinfection interference, with preinfection of cells with ALV-A, but not ALV-B or ALV-J, blocking subsequent JS11C1 infection. Finally, direct binding of JS11C1 and Tva was demonstrated by preincubation of the virus with soluble Tva, which substantially decreased viral infectivity in susceptible chicken cells. Collectively, these findings indicate that JS11C1 represents a new and bona fide ALV subgroup that utilizes Tva for cell entry and binds to a site other than that for ALV-A.IMPORTANCE ALV consists of several subgroups that are particularly characterized by their receptor usage, which subsequently dictates the host range and tropism of the virus. A few newly emerging and highly pathogenic Chinese ALV strains have recently been suggested to be an independent subgroup, ALV-K, based solely on their genomic sequences. Here, we performed a series of experiments with the ALV-K strain JS11C1, which showed its dependence on the Tva cell surface receptor. Due to the sharing of this receptor with ALV-A, both subgroups were able to interfere with superinfection. Because ALV-K could become an important pathogen and a significant threat to the poultry industry in Asia, the identification of a specific receptor could help in the breeding of resistant chicken lines with receptor variants with decreased susceptibility to the virus.
Keywords: virové receptory; internalizace viru; Receptors, Virus; druhová specificita; náchylnost k nemoci; virus ptačí leukózy; Animals; fibroblasty; host range; křeček rodu Mesocricetus; Species Specificity; Tva; Chickens; Avian Proteins; Cell Line; Mesocricetus; retrovirus receptor; zvířata; resistance/susceptibility to retrovirus; superinfection interference; kur domácí; Avian Leukosis Virus; Disease Susceptibility; Fibroblasts; Virus Internalization; buněčné linie; ptačí proteiny; ptačí leukóza; Avian Leukosis; avian leukosis virus K